PERENCANAAN PEMELIHARAAN IRIGASI D.I. POSSO KECAMATAN KWANDANG KABUPATEN GORONTALO UTARA - Fuad, Moh. Januar; Latif, Haris Z.; Djau, Bambang; Madjid, Siskawati; Mahmud, Abdul Muiz (Universitas Bina Taruna Gorontalo, 2024)
In spurring increased regional agricultural production, improving the irrigation network is the lifeblood of regional economic growth. It is hoped that handling the irrigation network will be able to stimulate agricultural production and restore the welfare of farmers in order to improve the economy while protecting the environment. As a first step in improving, maintaining and rehabilitating irrigation networks, careful planning is needed to obtain work data according to implementation standards and specifications. Posso Irrigation Area is one of the irrigation areas under the authority of the North Gorontalo Regency Government which is located in Kwandang District. Condition of irrigation network D.I. Posso is currently experiencing a decline in function and capacity due to sediment buildup and channel conditions that require maintenance. With a channel length of 1,381 meters that requires maintenance and cleaning of sediment and requires a physical budget of IDR 186,000,000.00 (One Hundred and Eighty Six Million Rupiah), which is expected to restore the function of the channel in the irrigation network Posso.